Sustainable Aquafeed Formulations Containing Insect Larval Meal and Grape Marc for the New Zealand Farmed Abalone - Natalia Bullon; Andrea C. Alfaro; Moganakumaar Manivannan; Seyedehsara Masoomi Dezfooli; Ali Seyfoddin (Aquaculture Nutrition)
The aquaculture industry has been criticised for the excessive use of fish meal (FM) in feeds due to the utilisation of wild fish in the formulation and the exacerbation of overfishing marine resources. Land-based abalone aquaculture mainly uses commercial feeds (CFs) to promote faster growth, which include FM as a primary protein component. Alternative ingredients, such as insect meal (IM) and grape marc (GM) are potential candidates for FM replacement due to their suitable nutritional profile and sustainable production. This paper reports on a novel nutritional approach for the New Zealand farmed abalone, which replaces FM with IM by 10% and includes a waste by-product (GM) by 30% as a potential prebiotic source. The study was performed in two stages: (a) physico-chemical determination of diets delivered in an alginate matrix (experimental diets) and their stability in seawater compared to CF and (b) evaluation of growth and feed intake for the New Zealand black-foot abalone. There were significant differences between experimental diets and CF in terms of sinking rate, particle weight, and microscopic observations. Water stability of the experimental diets was increased by 50% in 24 and 48 hr compared to CF, producing less solid waste, and potentially reducing cleaning efforts in the farm. The inclusion of IM and GM did not compromise overall animal growth or their feed conversion ratio, however, further evaluation need to be explored in the future research. The findings revealed that the developed encapsulated feeds are a more stable food delivery method for Haliotis iris compared to the CF. Furthermore, both IM and GM can be included in feed formulations as a more sustainable strategy without compromising weight and shell gains in the abalone farming.